2011
DOI: 10.1158/1535-7163.mct-10-0991
|View full text |Cite
|
Sign up to set email alerts
|

Truncated ErbB2 Expressed in Tumor Cell Nuclei Contributes to Acquired Therapeutic Resistance to ErbB2 Kinase Inhibitors

Abstract: ErbB2 tyrosine kinase inhibitors (TKI) block tyrosine autophosphorylation and activation of the full-length transmembrane ErbB2 receptor (p185ErbB2). In addition to p185ErbB2 truncated forms of ErbB2 exist in breast cancer cell lines and clinical tumors. The contribution of these truncated forms, specifically those expressed in tumor cell nuclei, to the development of therapeutic resistance to ErbB2 TKIs has not been previously demonstrated. Here we show that expression of a 95 kDa tyrosine phosphorylated form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 27 publications
0
41
1
Order By: Relevance
“…We have also shown that expression of an 85 kDa truncated form of ErbB2 (p85 ErbB2 ) that lacks the extracellular and transmembrane domains, is preferentially expressed in the nuclei of tumors that have become resistant to lapatinib [17]. Moreover, expression of p85 ErbB2 under the control of a heterologous promoter can render cells resistant to lapatinib and other ErbB2 targeted drugs in otherwise sensitive ErbB2+ breast cancer cells [17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have also shown that expression of an 85 kDa truncated form of ErbB2 (p85 ErbB2 ) that lacks the extracellular and transmembrane domains, is preferentially expressed in the nuclei of tumors that have become resistant to lapatinib [17]. Moreover, expression of p85 ErbB2 under the control of a heterologous promoter can render cells resistant to lapatinib and other ErbB2 targeted drugs in otherwise sensitive ErbB2+ breast cancer cells [17].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, expression of p85 ErbB2 under the control of a heterologous promoter can render cells resistant to lapatinib and other ErbB2 targeted drugs in otherwise sensitive ErbB2+ breast cancer cells [17]. Although p85 ErbB2 is tyrosine phosphorylation, an indication of its activated state, it is not inhibited by lapatinib (Figure 7) [17].…”
Section: Resultsmentioning
confidence: 99%
“…35 A recent study reported a nuclear localized truncated form of HER2, also 95 kDa in size, which retains phosphorylation and nuclear localization upon treatment with lapatinib. 36 The frequency and clinical significance of this finding are unknown at this time.…”
Section: Intrinsic Her2 Alterationsmentioning
confidence: 94%
“…The CTFs, which are generated at three methionine residues located on either side of the transmembrane domain, are found in the nucleus (Anido et al 2006;Xia et al 2011). These fragments promote cell migration ) and are reported to be oncogenic ).…”
Section: Translation-dependent Fragmentsmentioning
confidence: 99%